Fabrication and characterization of 4D-printed graphene oxide-reinforced PLA/PCL spinal cages for minimally invasive fusion surgery - Eryildiz, Meltem; Kadirhan, Ozge Altintas; Demirci, Mehmet; Karakus, Aleyna; Altan, Mihrigul Eksi (SPRINGERNATURE, 2025)
This study focuses on the development and characterization of 4D-printed, thermally activated polylactic acid (PLA)/polycaprolactone (PCL) spinal cages reinforced with graphene oxide (GO) for minimally invasive spinal fusion surgery. The primary objective is to fabricate biodegradable, shape memory cages that can be inserted in a compressed form and subsequently expand in situ upon thermal activation, enabling less invasive and more adaptable spinal implants. A 80:20 PLA/PCL blend was selected and reinforced with GO at varying concentrations (0.5-3 wt.%) to improve mechanical strength, thermal behavior, shape memory performance, and biodegradability. Among the formulations, 1 wt.% GO exhibited the most favorable combination of properties, achieving the highest tensile strength (23.6 MPa), compressive strength (40.7 MPa), and crystallinity (74.7%). Shape recovery tests demonstrated rapid and efficient re-expansion, especially under radiofrequency (RF) heating, which enabled uniform activation even in larger cage designs. Biodegradation studies showed progressive mass loss over 90 days, with GO accelerating degradation due to increased surface hydrophilicity, as confirmed by water contact angle measurements. Scanning electron microscopy (SEM) imaging indicated distinct changes in the microstructure with increasing GO content. The novelty of this study lies in the development of 4D-printed GO-reinforced PLA/PCL composite cages specifically tailored for minimally invasive spinal fusion. The results confirm that the proposed material and design strategy not only fulfills the key objectives of enhancing mechanical integrity, biodegradability, and shape memory functionality within a single implant platform, but also suggests strong potential for minimally invasive deployment and anatomical conformity in spinal fusion applications.
Keywords: 4D printing; Shape memory polymers; PLA/PCL-graphene oxide; Intervertebral cages; Spinal fusion; Minimally invasive surgery; POLYMER; NANOPARTICLE; COMPOSITE; Engineering; Materials Science